PICES Press, Vol. 21, No. 1, Winter 2013 (North Pacific Marine Science Organization (PICES), 2013)
•2012 PICES Science: A Note from the Science Board Chairman (pp. 1-6) ◾2012 PICES Awards (pp. 7-9) ◾GLOBEC/PICES/ICES ECOFOR Workshop (pp. 10-15) ◾ICES/PICES Symposium on “Forage Fish Interactions” (pp. 16-18) ◾The Yeosu Declaration, the Yeosu Declaration Forum and the Yeosu Project (pp. 19-23) ◾2013 PICES Calendar (p. 23) ◾Why Do We Need Human Dimensions for the FUTURE Program? (pp. 24-25) ◾New PICES MAFF-Sponsored Project on “Marine Ecosystem Health and Human Well-Being” (pp. 26-28) ◾The Bering Sea: Current Status and Recent Trends (pp. 29-31) ◾Continuing Cool in the Northeast Pacific Ocean (pp. 32, 35) ◾The State of the Western North Pacific in the First Half of 2012 (pp. 33-35) ◾New Leadership in PICES (pp. 36-39)